Caracterização e fatores preditivos no traumatismo raquimedular - Melo Neto, João Simão de (2016)
Spinal cord injury (SCI) has a negative impact on quality of life and healthcare costs. In recent years, with the age pyramid inversion, there is a high prevalence of SCI in the elderly. In addition, the most common SCI-related lesion is Traumatic brain injury (TBI). Treatment planning depends on many factors, and is determining for the presence of morbidity and mortality. These factors must be explored so that we can have investments for the prevention and treatment of these patients. Objectives: To identify the characteristics and clinical features of patients with SCI, specifically: the elderly; individuals with TBI-related SCI and individuals undergoing surgery. Methods: Prospective study, including 321 previously selected patients with SCI. Clinical and socio-demographic variables were collected and analyzed. Patients were characterized and morbidity and mortality predictors in the elderly (≥60 years) (n=62) were analyzed, as well as individuals who had TBI-related SCI (n=52), and patients undergoing surgical treatment (n=211). Results: The comparison between the two genders showed that women have compression fracture associated to the thoracolumbar transition region; men presented listhesis more related to cervical lesions and increase in the number of complications; the need for surgical intervention is higher in men; among other factors. When we compared older and younger patients (<60 years; n = 259), we found that the morphological diagnosis, compression fracture and dislocation fracture are more associated with age ≥60 to <60, respectively; elderly after SCI had a greater association with late hemodynamic instability. With regards to patients who had TBI-related SCI, male gender (85%), age group between 21-30 years (25%), individuals who have a common-law marriage status (56%), low level of education (69%) and the Roman Catholic religion (77%) had a higher number of patients. The cervical segment had higher risk of injury (RR=3.48, CI: 1.856 to 6.526; p <0.0001). The neurological status ASIA-E (52%), syndromic presentation of neck pain (35%) and mild TBI (65%) were the most frequent. Complications were observed in 13 patients, and pneumonia was the most prevalent (62%). Hospital stay was significantly higher (20±28 days), and 17% of patients died. Men (RR=2.513, CI: 1.777 to 3.554; p=0.028) and individuals exposed to car accidents (RR=1.91, CI: 1.00 to 1.579; p=0.022) showed a greater risk to suffer these lesions concomitantly. Furthermore, these patients had a 2.48 (CI: 1.372 to 4.477; p<0.01) higher risk of death than patients with SCI alone. Finally, regarding the choice of treatment, fall and upper cervical and lumbosacral injuries were associated with conservative treatment. Patients with lesions in the lower cervical area, worse neurological status and unstable lesions were associated with surgery. Complications in the postoperative period occurred mainly in patients undergoing surgery. Afterwards, we assessed whether age influenced the characteristics of patients undergoing surgery. Subjects <60 years of age were associated with motorcycle accidents and the morphologic diagnosis of injury was listhesis. Subsequently, we analyzed the influence of gender on the characteristics of these patients. Women who had car accidents were associated with surgery. Women were associated with paraparesis and morphologic diagnosis of burst fracture, especially in the thoracolumbar and lumbosacral transition. Men who had TBI and thoracic trauma were related to surgery. These individuals had a worse neurological status and were associated with complications. Men and cervical region were the most affected and therefore, these patients were analyzed separately (n = 92). The presence of complications increases hospital stay. Patients with simultaneous morphological diagnosis, worse neurological status, quadriplegia and sensorimotor changes had more complications. Mortality was higher in cases with clinical pneumonia and thoracic trauma. Conclusion: There are clinical and demographic factors that are specific to the elderly, as well as to patients who have had TBI-related SCI and individuals undergoing surgical treatment. The understanding of these factors enables investments in prevention, rehabilitation and treatment aiming at reducing morbidity and mortality, losses in quality of life and hospital service expenditures.